From Personal Wound to Professional Resilience: A Phenomenological Study of Working Women’s Career Resilience After Relational Betrayal - Epsilandri Septyarini (SAJMR : Southeast Asian Journal of Management and Research, 2026)
This study aims to explore how working women develop career resilience after experiencing relational betrayal in marriage. Using a qualitative phenomenological approach, data were collected through semi-structured interviews with four working women from different professional backgrounds, including a lecturer, a communication professional, a teacher, and an employee of a state-owned enterprise. The data were analyzed using thematic analysis supported by the Gioia data structure, consisting of first-order concepts, second-order themes, and aggregate dimensions. The findings reveal that relational betrayal becomes a critical life event that disrupts emotional stability, trust, self-perception, and professional functioning. However, work serves as a survival space, a source of self-worth, and an anchor for rebuilding professional identity. Six main dimensions emerged from the analysis: emotional disruption, professional survival, reclaiming professional identity, supportive recovery environment, women empowerment, and career resilience. This study contributes to human resource management literature by showing that career resilience is shaped not only by organizational pressures, but also by personal crises that affect employees’ psychological resources and work functioning.